Peranan Keaktifan Ibu Dalam Kegiatan Posyandu Dengan Status Gizi Balita Untuk Menunjang Sistem Informasi Perkembangan Balita - Yustina Retno Wahyu Utami, Sri Hariyati Fitriasih, Sri Siswanti (Jurnal Ilmiah SINUS, 2014)
Posyandu at Desa Banaran not only serve toddlers, but included for adults and elderly health counseling. This study analyzed the relationship between maternal nutritional and activity in neighborhood health center. The research method used descriptive analysis. Based on questionnaires distributed to 75 women as respondents and 10 volunteers, found that the parents especially the mother's role in the nutrition of toddlers is 82%, a factor of volunteer and medics must actively participate in the nutrition of toddlers which amounted to 89.44%, the education level affects the nutrition is 73%, the economic level impact on nutrition of toddlers by 89.44%. In addition, this study also result the design of nutrition monitoring information system. Keyword: questionnaire, mother’s activity in posyandu, nutrition of toddlers